Passing Learning Results By Applying Pairing Strategies In Football Games - Saleh, M. Sahib; Syahruddin, Syahruddin; Saleh, Muhammad Syahrul; Bismar, Ahmad Rum; As, Hasbunallah. (Journal Coaching Education Sports, 2024)
The research is a descriptive quantitative study that aims to determine the learning outcomes of students by applying a paired strategy to students of SDN Mamajang 1 Makassar. The independent variable in this study is to analyze the learning outcomes of soccer passing, while the dependent variable is to determine the results of passing in soccer games using a paired strategy. The population in this study were all fifth grade students of SDN Mamajang 1 Makassar as many as 21 students, Based on the data from the research results, the data analysis obtained the average learning outcomes of passing class V students of SDN Mamajang 1 Makassar of 20.33 showed a good category, then the research data and the classical assumption test and hypothesis testing of the paired passing model obtained data with an average value of 85.48. In accordance with the results of data analysis, it shows that the results of passing learning are supported by the success of the paired passing strategy with a contribution of 82% so that it can be concluded that the application of paired strategies can improve the passing of fifth grade students of SDN Mamajang 1 Makassar.